Pilot production of ulvans from Ulva sp. and their effects on hyaluronan and collagen production in cultured dermal fibroblasts. (10th February 2017) - Adrien, Amandine; Bonnet, Antoine; Dufour, Delphine; Baudouin, Stanislas; Maugard, Thierry; Bridiau, Nicolas
Highlights: A sulfated polysaccharide ulvan was extracted from Ulva sp. and purified. Neither acids nor solvents were used for the extraction and purification steps. A depolymerization method of ulvan using ion exchange resin was developed. The structure and composition of different molecular weight ulvans were assessed. These ulvans had strong activator effects on hyaluronan production by fibroblasts. Abstract: Ulvans from Ulva sp. were tested for their potential cosmetic properties on human dermal fibroblasts. The crude ulvans (ULVAN-01, 57 kDa), extracted using a patented acid- and solvent-free process, were subjected to depolymerization using ion exchange resin to obtain a low molecular weight ulvan (ULVAN-DEP, 4 kDa). The biochemical characterization and UHPLC-HRMS analyses of these extracted ulvans showed that they were of high purity and predominantly composed of a repeated ulvanobiouronic acid disaccharide. Fibroblast proliferation, as well as hyaluronan and collagen release were assessed, demonstrating that ULVAN-01 reduced fibroblast proliferation rate while ULVAN-DEP had no significant effect. Both ulvans were ineffective to induce collagen production but induced a significant increase in hyaluronan production, with a strong influence of the molecular weight. Thus, crude and depolymerized ulvans had different metabolic activities on dermal fibroblasts, which makes them promising to envisage further development in the skin care field.